Gastronomia Algarvia/Dieta Mediterrânica? - Braz, Nídia (2014)
The Mediterranean Diet concept was formulated during the sixties, in association with the food consumption pattern of Mediterranean areas that produced olive oil and shared common health styles. These areas, besides their own cultural and religious differences, share common food habits, such as: - The use of olive oil (supplier of monounsaturated fatty acids and antioxidants); - The abundant use of cereals, mainly under the form of excellent quality bread, flour and pasta (providing fibre and energy); - Large and variegate consumption of fruit (fresh and dried), nuts and vegetables (colourful, rich in fibre, antioxidants and other protective materials); - Abundant use of herbs and spices (rich in antioxidants and other protective materials); - Simple culinary methods, using short cooking times and low temperatures (which enhance the preservation of food nutritional and sensorial characteristics). The Mediterranean Diet reflects a set of characteristics that make it internationally recognized as a health promoter eating pattern, where the relation between monounsaturated and saturated fatty acids is highly advantageous for the former, fibre, vitamins and natural antioxidants intake is high, together with a low consumption of animal protein and salt. The obtained results show contents in protein, lipid and carbohydrates very adequate to the “DRI”; The relation between mono and saturated fatty acids (40:9) should be emphasised, together with the high fibre content. Protective nutrients show remarkable results, with a wide variety of vitamins and minerals, in particular Vitamin A, complex B vitamins, biotin, vit. E, folic acid, iron, manganese and selenium, that are widely recognised as important antioxidants and responsible for the good function of the immune system. In conclusion, tomato soup, consumed traditionally as a poor meal, shows to be a health promoter nutritionally complete recipe.